SUBALTERNITAS PEREMPUAN TIONGHOA DALAM NOVEL MEI MERAH 1998: KALA ARWAH BERKISAH - Fadhilah Ayu Wijayanti; Syamila Isyqi Alayya; Dwi Susanto (Sunan Kalijaga State Islamic University Yogyakarta, 2024)
This study aims to examine the subject of women in colonial discourse by natives through the novel Mei Merah 1998: Kala Arwah Berkisah. To achieve this goal, descriptive qualitative is used as a research method. The data source is the novel Mei Merah 1998: Kala Arwah Berkisah (2018) by Naning Pranoto and all information related to the research topic. The research data ranges from language and sentences to thoughts in the text of the novel which contains narratives of female subjects who experience oppression and other related data. Data collection techniques are done by reading and taking notes. This research shows that Chinese women in Indonesia are in a subaltern position in the societal hierarchy. These women experienced double oppression, from their identity as Chinese under native domination and from their position as women under male domination. The events of May 1998 were proof of colonialism against ethnic Chinese women. The voice of the silenced minority group is attempted by the author to construct through the narration of the female subject in the novel. These Chinese females in this narrative experience ambivalence and mimicry as a way of resisting colonial discourse from the dominating natives.